Rewriting a History of Open Universities: (Hi)stories of Distance Teachers - Lee, Kyungmee (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
This article reports eight distance teachers’ stories about teaching at two open universities over the past two decades with a focus on their perceptions and feelings about the changes in their teaching practice. This qualitative study employed a methodological approach called the autoethnographic interview, aiming to document more realistic histories of the open universities and to imagine a better future for those universities. As a result, the paper presents autobiographical narratives of distance teachers that dissent from the general historical accounts of open universities. These narratives are categorized into three interrelated themes: a) openness: excessive openness and a lost sense of mission; b) technological innovation: moving online and long-lasting resistance, and c) teaching: transactional interactions and feelings of loneliness. The paper then presents a discussion of useful implications for open universities, which can serve as a starting point for more meaningful discussions among distance educators in a time of change.